International Trade in Muslim-Majority Countries and Volatility of The Dollar Exchange Rate - Desmintari; Raden Parianom; Risna Triandhari; Bryan Listyanto (Interdiciplinary Journal and Hummanity (INJURITY), 2023)
The study was to examine the relationship between the volatility of the dollar exchange rate on international trade variables, namely exports and imports, in 3 Muslim-majority countries. This study analyzes the possibility that the volatility of the dollar exchange rate can hamper the economy of a country. The method used is the Autoregressive Distributed Lag and Error Correction Model (ARDL-ECM) to analyze the short-term and long-term relationship between the volatility of the dollar exchange rate against international trade in Indonesia, Pakistan, and Turkey. And to see the causality relationship between variables, the Granger-Causality method is used. The data used are monthly data for the period January 2006 to December 2021. From this research, it can be seen that in the long term there is no relationship between exchange rate volatility and export performance except in Turkey. Meanwhile, there is a relationship between exchange rate volatility and import performance in Pakistan and Turkey. In the short term in the export dependent model, Turkey is the country that takes the longest to respond to shocks to international trade, while in the import dependent model, Indonesia takes the longest to respond to shocks and Pakistan is the fastest country.